Compositionally Graded Absorber for Efficient and Stable Near‐Infrared‐Transparent Perovskite Solar Cells. Issue 3 (5th January 2018) - Fu, Fan; Pisoni, Stefano; Weiss, Thomas P.; Feurer, Thomas; Wäckerlin, Aneliia; Fuchs, Peter; Nishiwaki, Shiro; Zortea, Lukas; Tiwari, Ayodhya N.; Buecheler, Stephan
Abstract: Compositional grading has been widely exploited in highly efficient Cu(In, Ga)Se2, CdTe, GaAs, quantum dot solar cells, and this strategy has the potential to improve the performance of emerging perovskite solar cells. However, realizing and maintaining compositionally graded perovskite absorber from solution processing is challenging. Moreover, the operational stability of graded perovskite solar cells under long‐term heat/light soaking has not been demonstrated. In this study, a facile partial ion‐exchange approach is reported to achieve compositionally graded perovskite absorber layers. Incorporating compositional grading improves charge collection and suppresses interface recombination, enabling to fabricate near‐infrared‐transparent perovskite solar cells with power conversion efficiency of 16.8% in substrate configuration, and demonstrate 22.7% tandem efficiency with 3.3% absolute gain when mechanically stacked on a Cu(In, Ga)Se2 bottom cell. Non‐encapsulated graded perovskite device retains over 93% of its initial efficiency after 1000 h operation at maximum power point at 60 °C under equivalent 1 sun illumination. The results open an avenue in exploring partial ion‐exchange to design graded perovskite solar cells with improved efficiency and stability. Abstract : A compositionally graded perovskite absorber is designed by partial ion‐exchange reaction to improve charge collection and suppress interfacial recombination, which leads to improved efficiency and operational stability in near‐infrared‐transparent planar perovskite solar cells. The non‐encapsulated graded perovskite device retains over 93% of its initial efficiency after 1000 h operation at maximum power point at 60 °C under equivalent 1 sun illumination.